2018
DOI: 10.1016/j.ihj.2017.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Does resting heart rate measured by the physician reflect the patient’s true resting heart rate? White-coat heart rate

Abstract: Our study brings to light an exciting idea that could have a major therapeutic and maybe prognostic impact in cardiology: resting HR measured by the physician in consultation does not reflect true resting HR. This must be taken into account to adapt treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…15,10 However, previous studies have shown that HRs measured in clinical settings may not be representative of real-world HR and may be biased by the particular clinical conditions for which the ECGs were ordered. 1,3 For example, a “white-coat” effect can increase HR, 11 leading to false elevation. Furthermore, ambulatory, real-world HR, has been found to correlate significantly more with mortality than resting heart rate obtained in the clinical setting, 12 suggesting the need to update HR norms to reflect real-world, remotely obtained values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,10 However, previous studies have shown that HRs measured in clinical settings may not be representative of real-world HR and may be biased by the particular clinical conditions for which the ECGs were ordered. 1,3 For example, a “white-coat” effect can increase HR, 11 leading to false elevation. Furthermore, ambulatory, real-world HR, has been found to correlate significantly more with mortality than resting heart rate obtained in the clinical setting, 12 suggesting the need to update HR norms to reflect real-world, remotely obtained values.…”
Section: Discussionmentioning
confidence: 99%
“…2 Whereas our 95th percentile was similar among those < 40 years old (104 bpm in both cohorts), among those > 40 years old, we found a lower 95th percentile (100 bpm vs 104 bpm), 2 which may be due to our repeat measurements taken outside of the clinic setting, decreasing variability, and minimizing any “white-coat” heart rate effect. 11 Furthermore, we described the circadian evolution of real-world HR, which allows us to interpret these values according to the time of day. 13 We observed that HR-PPG and HRV levels decline with age.…”
Section: Discussionmentioning
confidence: 99%
“…The second one refers to the caution which should be used in the interpretation of data since the %HRR metric was based on the commonly accepted formula for estimating the maximum heart rate, which has its own limitations [33]. Also, an ambulatory trial found heart rates at rest lower when self-measured at home compared to those measured under expert observation [34]. Obviously, such an effect will probably lead to an underestimation of job’s difficulty, the same way the exposure to high thermal stress will.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should invest in validating predictions for stroke survivors. Furthermore, physiological resting values were measured pre-exercise, possibly causing excitement or stress (similar to a white-coat effect 53 ), slightly overestimating true resting values and underestimating percentages of heart rate reserve.…”
Section: Discussionmentioning
confidence: 99%